Basic geological mapping - Lisle, Richard J.; Brabham, Peter; Barnes, J. W. (John Wykeham) 1921- .; Barnes, J. W. (John Wykeham) 1921- (Chichester, West Sussex Wiley, 2011)
"Basic Geological Mapping, 5th Edition is an essential basic guide to field techniques in mapping geology. Now completely revised and updated the book retains the concise clarity which has made it an indispensable instant reference in its previous editions. It provides the reader with all the necessary practical information and techniques that they will need while carrying out work in the field, covering a wide spectrum of different conditions, needs and types of countries. This edition covers new developments in technology including Google Earth and the use of GPS. This is an ideal field guide to geological mapping for 2nd/3rd year undergraduates of Geology, Hydrogeology and Geological Engineering"--Provided by publisher.
"Basic Geological Mapping, 5th Edition is an essential basic guide to field techniques in mapping geology"--Provided by publisher.
Revised edition of: Basic geological mapping / John W. Barnes, with Richard J. Lisle. Fourth edition.
Includes bibliographical references (pages 205-208) and index.
Keywords: Geological mapping; SCIENCE / Earth Sciences / Geology